On love and death - Byers, Brooklyn (My University, 2024)
"On Love and Death" is a short story recounting the brief meetings of a personified Love and Death. The two meet on three occasions, from the beginning to the end of time. Without dialogue or biological classification, the story tells of life beyond the confines of humankind's perspective and implies a destructive evolutionary process by which the two suffer.
Keywords: short stories